O narrado em Antônio Carlos Viana: uma contradição - Fonseca, Cristiane Mirtes da (2013)
The fundamental interest of this research on the figure of the narrator. It examines three books of short stories by Antônio Carlos Viana - O meio do mundo, Aberto está o inferno e Cine Privê - and a tale novel published in book este seu olhar, organized by Professor Regina Zilberman, putting into relief the ambiguous character of his first-person narrators, especially to those who are classified as “boy-narrator” and the coexistence of an adult narrator during the speech by character throughout the narrative .We also sought to establish dialogue between the social and literary discourse, presenting aesthetic aspects that point to the awakening reflective of ailments, whether physical of psychological, they are subjected to a portion of society, without being pamphleteer. Therefore, we sought the aid theoretical literature already sanctioned by literary criticism, but mostly gave priority to the text of the author. That is, the readings focus on the works, without the worry of theoretical explanations that no maintain relationships with immediate issue discussed.